Efektifitas Pengunaan Batu Gamping Sebagai Campuran Agregat Halus pada Base A - Winata, Carles Pandu (Jurnal Proyek Teknik Sipil, 2025)
Enggano Island is one of the areas in Bengkulu Province, located directly on the border with the Indian Ocean, making Enggano Island one of the outermost small islands in Indonesia. This island is one of the geographical areas where the soil contains lime, where limestone or what is often known as limestone is a non-metallic industrial mineral which has benefits as a raw material for cement, aggregate and asphalt. Considering that this island is a small island, it is very difficult to find mountain stone or river stone for Base A aggregate needs, because limestone is abundant on this island, this has encouraged researchers to conduct research on limestone as an additional material for fine aggregate in Base A. Research This aims to determine the CBR value after using limestone at 0%, 10%, 20% and 30%. CBR testing is carried out using the California Bearing Ratio (CBR) test method using a CBR penetration tool. The results of this research show that base A aggregate mixed with 0% limestone produces a CBR value of 94.84%, mixing 10% produces a CBR value of 95.34%. The addition of 20% produces a CBR value of 95.96%, and mixing 30% produces a CBR value of 96.62%. These results indicate that the addition of a limestone mixture as fine aggregate in base A can be used because the CBR value is greater than 90% and with the composition determined in this research